Letter (copy) : Mrs. Gwendolyn Adams - Citrine, Walter, 1887-1983
013-0125-001 Secretary's. WMC/HVT/FC/196. 6th December, 1939. The Rt. Hon Viscount Halifax, K.G.,G.C.S.I., M.P., The Foreign Office, Downing Street, S.W.1. Dear Lord Halifax, MRS. GWENDOLYN ADAMS. I am greatly obliged to you for your letter of the 5th instant and for your kind promise to investigate Mrs. Adams' [Adams de Puertas] case. I fully appreciate the difficulties in regard to the matter being pursued officially. Yours sincerely, General Secretary. 292/946/13/125